The immunocytochemical localisation and distribution of cytochrome P-450 in normal human hepatic and extrahepatic tissues with a monoclonal antibody to human cytochrome P-450. - Murray, G I (1988)
1. The localisation and distribution of cytochrome P-450 in human tissues has been studied by immunocytochemistry using a monoclonal antibody to a major form of human hepatic cytochrome P-450, P-450hA7, which is closely related to cytochromes P-450 HLp and P-450NF. 2. Strong immunoreactivity was identified in hepatocytes, columnar absorptive epithelial cells of the small intestine, polymorphonuclear leucocytes and their precursors in the bone marrow, and in mast cells. 3. Weak immunoreactivity was present in the proximal tubules of the kidney, pancreatic acini, gall bladder epithelium, squamous epithelium and sebaceous glands of the skin, interstitial cells of the testis and luteal cells of the ovary. 4. Immunoreactivity could not be demonstrated in the adrenal gland, placenta, colonic epithelium and alveolar type II cells and Clara cells of the lung.